Representasi Nilai Ekologi pada Kearifan Lokal Sendang dalam Buku Boyolali Kaya Cerita: Perspektif Ekokritik - Sabrina Tamimi; Chafit Ulya (Universitas Muhammadiyah Surakarta, 2026)
This research is motivated by the ecological crisis in Indonesia, marked by high levels of water pollution. Efforts to increase ecological awareness can be carried out through local wisdom stories with a sendang theme. This research aims to analyze ecological values in the book Boyolali Kaya Cerita with a sendang theme, including the stories of Sendang Kunti, Sendang Pitu, and Sendang Songo.This study employs a descriptive qualitative approach using content analysis methods and an ecocritical approach by Greg Garrard. Data were collected through reading and note-taking techniques and analyzed using an interactive model that includes data reduction, data presentation, and conclusion drawing. The results show that the value of the earth is the most dominant, followed by the values of dwelling and animals in equal proportions. The earth value indicates a strong presence of awareness, actions, and cooperation among humans in preserving environmental sustainability. Meanwhile, dwelling and animal values illustrate the interconnection between human life, habitation, and the existence of animals. In contrast, pollution and disasters are less prominent. This indicates that human actions threatening environmental sustainability are not the primary aspect of ecological values in the three sendang stories. These findings demonstrate that the book Boyolali Kaya Cerita with a sendang theme contains relevant ecological values that can encourage awareness in maintaining environmental sustainability.